Mediasi Hubungan Industrial Yang Melebihi Batas Waktu - Akni, Rigea Rema Nur (Lentera Hukum, 2015)
The number of disputes that arise in industrial relations is something that cannot be avoided even though ultimately it can be resolved through deliberation, mediation, conciliation, arbitration or court. In the law number 2 of 2004 concerning the settlement of industrial relations disputes, it has been stipulated that in the event of a dispute between the worker/laborer and the employer, the bipartite settlement must first be attempted. If the settlement through a bipartite fails, the an attempt is made to resolve the dispute through mediation. Mediatoin is a peaceful process whereby the disputing parties hand over the settlement to a mediator, namely someone who arrangers a meeting between two or more parties at odds to achieve a just outcome, without wasting too much money, but remains effective and fully accepted by the two the parties who have disputes voluntarily.Keyword : Dispute, Mediation, Industrial Relations